MENGUNGKAP ALASAN WAJIB PAJAK MENGIKUTI PROGRAM PENGUNGKAPAN SUKARELA - Susiyana, Eka; Faisol, Moh. (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2023)
PPS is an opportunity given by the state to tax amnesty participants in accordance with UU number 11 of 2016 who have not disclosed all net assets in a statement letter and provides an opportunity for individual taxpayers to disclose net assets that have not been reported in the 2020 annual tax return obtained from 2016 to 2020. This study aims to reveal the reasons why taxpayers follow PPS. This research method is a case study with documentary data type and primary data with interview and documentation techniques, where researchers conduct interviews with six informants. The data analysis techniques used in this study are data reduction, data presentation and conclusion drawing by testing the validity of data using triangulation techniques. The result of this study is that taxpayers follow PPS for the first reason, get the opportunity to declare assets and avoid sanctions; second, to have the opportunity to uncover treasures that have not been properly revealed; Third, comfort and guaranteed protection of property. The implication of the results of this study is that policies in the field of taxation such as TA and PPS become one of the alternatives in increasing compliance and awareness of taxpayers and maximizing tax revenue for the state.